Incidence, characteristics, and survival following cardiopulmonary resuscitation in the quaternary neonatal intensive care unit. (January 2017) - Foglia, Elizabeth E.; Langeveld, Robert; Heimall, Lauren; Deveney, Alyson; Ades, Anne; Jensen, Erik A.; Nadkarni, Vinay M.
Abstract: Background: The contemporary characteristics and outcomes of cardiopulmonary resuscitation (CPR) in the neonatal intensive care unit (NICU) are poorly described. The objectives of this study were to determine the incidence, interventions, and outcomes of CPR in a quaternary referral NICU. Methods: Retrospective observational study of infants who received chest compressions for resuscitation in the Children's Hospital of Philadelphia NICU between April 1, 2011 and June 30, 2015. Patient, event, and survival characteristics were abstracted from the medical record and the hospital-wide resuscitation database. The primary outcome was survival to hospital discharge. Univariable and multivariable analyses were performed to identify patient and event factors associated with survival to discharge. Results: There were 1.2 CPR events per 1000 patient days. CPR was performed in 113 of 5046 (2.2%) infants admitted to the NICU during the study period. The median duration of chest compressions was 2 min (interquartile range 1, 6 min). Adrenaline was administered in 34 (30%) CPR events. Of 113 infants with at least one CPR event, 69 (61%) survived to hospital discharge. Factors independently associated with decreased survival to hospital discharge were inotrope treatment prior to CPR (adjusted Odds Ratio [aOR] 0.14, 95% Confidence Interval [CI] 0.04, 0.54), and adrenaline administration during CPR (aOR 0.14, 95% CI 0.04, 0.50). Conclusions: Although it was not uncommon, the incidence of CPR was low (<3%) among infants hospitalized in a quaternary referral NICU. Infants receiving inotropic therapy prior to CPR and adrenaline administration during CPR were less likely to survive to hospital discharge.